Penerapan Metode Pendekatan Berdiferensiasi Menggunakan Aplikasi Kahoot pada Mata Pelajaran IPAS - Mukti, Wisnu Cahya; Huda, Choirul (STKIP Andi Matappa Pangkep, 2024)
Education today faces significant challenges in presenting relevant and engaging material to students with diverse backgrounds and needs. Differentiated instruction is a teaching strategy that tailors learning experiences to meet the unique needs of each student. Kahoot is an interactive platform that supports differentiated instruction by providing tools that allow teachers to create engaging and adaptive learning experiences. This study aims to investigate the impact of applying differentiated instruction methods using Kahoot in Social Studies subjects on students' motivation and learning outcomes. The research method used is qualitative descriptive. The subjects of this study are 28 fourth-grade students from SD Palebon 01. The results indicate that the majority of students showed high to very high motivation after participating in the learning activities using Kahoot. Only a small number of students had low motivation, and no students were classified in the very low motivation category. Overall, students' learning outcomes were very positive, with all students falling into the Good or Very Good categories.